1976
DOI: 10.17730/humo.35.2.u28u6162x3135482
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nutrition and Traditional Food Behavior in Haiti

Abstract: Rural Haitian nutrition has long been a matter of concern to health workers. The diet is seriously restricted and there is widespread malnutrition. This is especially striking among lactating women. The Haitian government, under François Duvalier, began comprehensive programs designed to alleviate some of the economic and technologic factors which limit the diet. An equally serious restricting influence on the diet, however, and an influence which has gone largely unnoticed, is the hot/cold classification of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Reasons for breastfeeding include that breastfeeding is the best nutrition for the baby, it is a ‘natural’ process, and it would develop a stronger, healthier baby (Thomas & DeSantis 1995). Earlier studies have showed that although there was a diversity of opinions over the nature of food taboos, diet was a central concern (Wiese 1976; Dempsey & Geese 1983; Harris 1987). Most significantly, it is clear that ‘eating well’ is critical for the quality of the breast milk (Roman 2007) as was the time at which it was consumed: a mother eating late in the day was believed to cause diarrhoea in the breastfed child (Kirkpatrick & Cobb 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for breastfeeding include that breastfeeding is the best nutrition for the baby, it is a ‘natural’ process, and it would develop a stronger, healthier baby (Thomas & DeSantis 1995). Earlier studies have showed that although there was a diversity of opinions over the nature of food taboos, diet was a central concern (Wiese 1976; Dempsey & Geese 1983; Harris 1987). Most significantly, it is clear that ‘eating well’ is critical for the quality of the breast milk (Roman 2007) as was the time at which it was consumed: a mother eating late in the day was believed to cause diarrhoea in the breastfed child (Kirkpatrick & Cobb 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Thus a number of foods may continue to be avoided for some time following the end of the traditional puerperium, due both to personal inclination and to infant feeding practices. -Studies elsewhere on puerperal dietary restrictions based on humoral pathology, including Malaysia (Wilson, 1973), India (Eichinger Ferro-Luzzi, 1974;Sundaraj and Pereira, 1975) and Haiti (Wiese, 1976), suggest that the postparturient woman may be seriously at risk nutritionally. Food avoidances during the postpartum period tend to be the most critical ones imposed on women, since they usually are imposed for the longest period of time and are applied concurrently to the largest number of food items.…”
Section: Discussionmentioning
confidence: 99%
“…17. Wiese (1976), King et al (1978), and others argued that inappropriate individual and cultural eating practices in Haiti may play important roles in maintaining lower nutrition levels than otherwise possible with available resources. The argument served as the basis for several nutrition education programs in Haiti.…”
Section: Notesmentioning
confidence: 99%